High-stability lithium-rich layered positive electrode material as well as preparation method and application thereof

By doping the lithium layer, transition metal layer and oxygen layer of the lithium-rich layered cathode material with low-cost anions and cations respectively, and using the sol-gel method to synthesize high-stability materials, the poor material performance and complicated processes in the existing technology are solved. problem, achieving efficient, stable electrochemical performance and thermal safety.

CN119340369APending Publication Date: 2025-01-21QINGDAO INST OF BIOENERGY & BIOPROCESS TECH CHINESE ACADEMY OF SCI

Patent Information

Application Number
CN202411498549.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

During the industrialization process, the existing lithium-rich layered cathode materials face the problems of low charge and discharge efficiency for the first time, poor cycle stability, serious voltage attenuation and poor rate performance. The doping elements are costly and complex, making it difficult to achieve structural stability and Improved thermal stability.

Method used

The sol-gel method is used to synthesize highly stable lithium-rich layered cathode materials. By doping the lithium layer, transition metal layer and oxygen layer with low-cost and naturally abundant anions and cations respectively, the structural stability and electrochemistry of the material are achieved. Performance improvements.

Benefits of technology

Achieved the preparation of highly stable lithium-rich layered cathode materials, showing high first charge and discharge efficiency, long cycle life, outstanding rate performance and excellent thermal safety, overcoming the high cost and process in the existing technology Complex issues.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340369A_ABST
    Figure CN119340369A_ABST
Patent Text Reader

Abstract

The invention relates to a secondary energy storage battery, in particular to a high-stability lithium-rich layered positive electrode material as well as a preparation method and application thereof. The lithium-rich layered positive electrode material is Li < 1 + x-a > A T < 1-x-b > B O < 2-c > C < c >, xlt; 1, 0lt; a is less than or equal to 0.1, 0lt; b is less than or equal to 0.1, 0lt; c < = 0.1; wherein A is a doping element in the lithium layer, B is a doping element in the transition metal (TM) layer, and C is a doping element in the oxygen layer. The electrochemical redox reversibility of the lithium-rich layered positive electrode material is enhanced through the synergistic modification of the lithium layer, the transition metal layer and the oxygen layer in the obtained positive electrode material, the transformation from the layered structure to the spinel structure in the cyclic process is inhibited, and the structural stability of the material is improved. The modified material has the advantages of high first charge-discharge efficiency, high reversible specific capacity, long cycle life, outstanding rate capability, high thermal stability and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a secondary energy storage battery, in particular to a high-stability lithium-rich layered positive electrode material and a preparation method and application thereof. Background Art

[0002] As a new type of efficient secondary energy storage battery, lithium-ion batteries have been widely studied due to their advantages such as high voltage, high energy density, safe operation, and no memory effect. They have been widely used in various portable electronic devices, electric vehicle industries, etc., and have put forward higher requirements for performance indicators such as cycle life, energy density, and thermal safety of lithium-ion batteries. Among them, the development of high-performance positive electrode materials for lithium batteries is the key to achieving the comprehensive performance improvement of lithium-ion batteries.

[0003] The actual specific capacity of currently commercialized cathode materials (such as layered LiCoO2, spinel LiMn2O4, olivine LiFePO4 and ternary materials, etc.) is generally low (<200mAh / g), which limits the development of the next generation of new power batteries (energy density ≥400Wh / kg) from the material level. As a new cathode material with great development potential, the lithium-rich layered oxide material xLi2MnO3·(1-x)LiTMO2 (TM=Ni, Mn, Co, etc.) has attracted extensive attention from the scientific research and industry due to its high discharge specific capacity (>250mAh / g), high energy density (~1000Wh / Kg) and low cost. However, the industrialization of lithium-rich layered cathode materials is still hindered by low first charge and discharge efficiency, poor cycle stability, severe voltage decay and poor rate performance. More importantly, the high charging voltage operating conditions and the characteristics of anion oxygen participating in the reaction also increase the safety risks of lithium batteries. There are many public response strategies to these problems, but they still have their own corresponding shortcomings.

[0004] CN114620775A discloses a double anion co-doped lithium-rich manganese-based composite material, a preparation method and an application thereof, wherein a mixed solution of a fluorine source and a sulfur source is used to modify a lithium-rich manganese-based positive electrode finished material synthesized by a sol-gel method to obtain a fluorine- and sulfur-co-doped lithium-rich manganese-based composite material. In fact, this is a double anion surface doping method, which cannot effectively regulate the bulk structure of the positive electrode material, and the effect of improving the thermal stability of the lithium-rich manganese-based positive electrode material is limited.

[0005] CN112652771A discloses a multi-anion doped single crystal high nickel positive electrode material and a preparation method thereof. Based on a single crystal high nickel positive electrode precursor, a single anion doped material is first prepared by a liquid phase method, and then the obtained single anion doped material is doped with a second anion by a gas phase method, and finally a multi-anion doped (sulfur, fluorine or chlorine) high nickel single crystal positive electrode material is obtained, which improves the rate performance of the material. However, this method is a multi-step doping method with a complex process. The doping elements and the main material cannot be mixed at the atomic level, the doping uniformity is difficult to ensure, and the coordinated regulation of the structural stability of the positive electrode material cannot be achieved.

[0006] CN113764647A discloses a zirconium and multi-anion doped modified ternary positive electrode material precursor and a preparation method thereof, wherein an aged slurry of the ternary positive electrode main material is first obtained by a coprecipitation method, and then a zirconium source and a multi-anion source (sulfur, fluorine, chlorine or bromine) are injected into the obtained slurry to continue coprecipitation, thereby obtaining a zirconium and multi-anion bulk phase doped ternary positive electrode precursor with a stable structure. However, in this method, the anions cannot react with the NaOH precipitant to precipitate, the anion doping source and the main material source are in different phases, and it cannot be guaranteed whether the doping is in the bulk phase or on the surface.

[0007] CN114702082A discloses a method for realizing dual-position co-doping modification of lithium layer doped with Na and transition metal layer doped with Nb in lithium-rich manganese-based positive electrode materials by sol-gel method, which significantly improves the discharge specific capacity and voltage retention rate. However, this method uses the high-cost Nb element, which is not conducive to commercial application; the dual modification of lithium layer and transition metal layer can indeed enhance the structural stability and electrochemical performance of the material, but the effect on the oxygen layer may not be significant, so there is still a lot of room for improvement.

[0008] In general, previous doping modification strategies usually have many problems such as monotonous action sites, high cost of doping elements, complex doping process or uneven distribution of doping elements, and the effect on improving the structural stability and thermal stability of positive electrode materials is not significant. Therefore, the development of positive electrode material modification and preparation methods with simple preparation process, low cost and significant improvement effect is an urgent technical need to promote the rapid development and industrial application of high specific energy, high safety lithium-rich manganese-based positive electrode materials. Summary of the invention

[0009] The present invention aims to provide a high-stability lithium-rich layered positive electrode material and a preparation method and application thereof.

[0010] To achieve the above purpose, the present invention adopts the following technical solution:

[0011] A highly stable lithium-rich layered positive electrode material, the lithium-rich layered positive electrode material is Li 1+x-a A a TM 1-x-b Bb O 2-c C c , where 0 < x < 1, 0 < a ≤ 0.1, 0 < b ≤ 0.1, 0 < c ≤ 0.1; wherein, the A is a doping element in the lithium layer, B is a doping element in the transition metal (TM) layer, and C is a doping element in the oxygen layer.

[0012] The A is selected from one or more of monovalent metal ions, the TM is selected from one or more of Mn, Ti, Fe, Co, Ni, the B is selected from one or more of B, Mg, Al, Si, P, Ca, Cu, Zn, Zr, Se, and the C is selected from one or more of S, F, Cl, Br, I.

[0013] The A is selected from one or more of Na, K, Rb, Cs.

[0014] A method for preparing the high-stability lithium-rich layered cathode material as described above, according to the stoichiometric ratio of the material, the main body source in the cathode material and the doping elements in each main body source are put in at the same time, and the high-stability lithium-rich layered cathode material is obtained by synthesis through the sol-gel method; wherein the main body source is a lithium source and a transition metal source.

[0015] Furthermore,

[0016] 1) Precursor synthesis: The lithium source in the lithium layer, the transition metal source in the transition layer and the doping elements in the above two metal layers are uniformly dispersed in deionized water according to the stoichiometric ratio in the chemical formula Li 1+x-a A a TM 1-x-b B b O 2-c C c to obtain solution A; the element source used for doping in the oxygen layer is uniformly dispersed in deionized water according to the stoichiometric ratio in Li 1+x-a A a TM 1-x-b B b O 2-c C c to obtain solution B; the soluble organic acid source used as a chelating agent is uniformly dispersed in deionized water to obtain solution C; solution A and solution B are slowly put into solution C at the same time to obtain solution D, and the pH of solution D is adjusted to 6-10, dried and pulverized to obtain the precursor;

[0017] 2) Precursor sintering: The precursor is placed in a specific atmosphere at 400-600 °C for 3-8 h, and then sufficiently ground into a uniform powder; the obtained powder is placed in a specific atmosphere at 600-800 °C for 3-12 h, and then heated to 800-1000 °C for high-temperature sintering for 8-20 h to obtain the high-stability lithium-rich layered cathode material (Li 1+x-a A a TM1-x-b B b O 2-c C c ).

[0018] The lithium source is one or more of lithium hydroxide, lithium citrate, lithium nitrate, lithium acetate, lithium sulfate, lithium fluoride, and lithium carbonate;

[0019] The transition metal source is one or more of acetates, nitrates or hydroxides containing Mn, Fe, Co and Ni elements;

[0020] The transition metal source containing the Ti element is one or more of tetrabutyl titanate, titanium hydroxide, ammonium titanyl oxalate and titanium dioxide.

[0021] The doping element of the lithium layer can be selected from one or more of acetates, nitrates, carbonates or hydroxides containing Na, K, Rb or Cs elements;

[0022] The doping element of the transition metal layer can be selected from one or more of acetates, nitrates, oxides or hydroxides containing Mg, Al, Ca, Cu, Zn and Zr.

[0023] The doping element B of the transition metal layer may be one or more of boric acid, boron oxide and ammonium pentaborate;

[0024] The doping element Si of the transition metal layer can be selected from one or more of lithium metasilicate and quaternary ammonium silicate.

[0025] The doping element P of the transition metal layer may be selected from one or more of phosphoric acid, pyrophosphoric acid, diammonium hydrogen phosphate, ammonium phosphate and phosphorus pentoxide.

[0026] The doping element Se of the transition metal layer may be selected from one or more of selenium dioxide, selenium trioxide, selenic acid and ammonium selenate;

[0027] The doping element of the oxygen layer may be a soluble ammonium salt or lithium salt containing F, Cl, Br, or I;

[0028] The doping element S of the oxygen layer may be selected from one or more of 2-mercaptopropionic acid, lithium sulfide, ammonium sulfide, and thiourea.

[0029] The soluble organic acid source is one or a mixture of tartaric acid, oxalic acid, citric acid, and maleic acid, and the molar ratio of the carboxyl group in the organic acid to the total metal ions in the precursor is (1-10):1.

[0030] The solution D is adjusted to a pH value and then heated in a water bath at 60-100° C. for 6-20 h, evaporated to dryness, dried at 80-140° C., and crushed to obtain a precursor.

[0031] In the step 2), the specific atmosphere is oxygen or air, and the heating rate is 0.5-5°C / min.

[0032] Advantages of the present invention

[0033] (1) Compared with the previous doping modification strategies, the lithium-rich layered cathode material of the present invention adopts different low-cost, high-natural-abundance anions and cations to dope the lithium layer, transition metal and oxygen layer respectively, thereby synergistically enhancing to obtain a structurally stable, high-capacity lithium-rich layered cathode material, thereby achieving a comprehensive improvement in electrochemical performance and thermal safety, thereby overcoming the problems of monotonous action sites and high cost of doping elements existing in previous technologies.

[0034] (2) The preparation process of the present invention adopts a liquid phase chemical synthesis method represented by the sol-gel method to achieve the synergistic modification of the lithium layer, the transition metal layer and the oxygen layer, and the main source of the material and the doping source raw material are simultaneously put into the chemical reaction. Among them, the organic acid can chelate various metal elements to ensure that the metal elements are evenly dispersed in the solution. In addition, the sol-gel method adopted by the present invention can achieve the element doping of the lithium layer, the transition metal layer and the oxygen layer at one time, avoiding the shortcomings of other synthesis methods such as complex operation, difficult to control the element doping site, and uneven doping, and realizes the atomic-level dispersion between the main material raw material and the doping element source, which has the advantages of high product purity, uniform distribution of doping elements, controllable stoichiometric ratio, strong adjustability of structure and performance, and environmental friendliness.

[0035] (3) The high-stability lithium-rich layered cathode material prepared by the present invention exhibits excellent electrochemical properties such as high initial charge and discharge efficiency, long cycle life, outstanding rate performance and small battery polarization. At the same time, the high-stability lithium-rich layered cathode material also exhibits excellent thermal safety. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 A scanning electron microscope (SEM) of the high-stability lithium-rich layered positive electrode material prepared in Example 1 of the present invention;

[0037] Figure 2 The powder X-ray diffraction (XRD) spectrum of the high-stability lithium-rich oxide positive electrode material prepared in Example 2 of the present invention;

[0038] Figure 3 Cycling performance of button-type lithium-ion batteries assembled from the high-stability lithium-rich oxide positive electrode material prepared in Example 4 of the present invention and Comparative Examples 1, 2, 3 and 4;

[0039] Figure 4 Comparison of the cycling performance of the high-stability lithium-rich oxide positive electrode material prepared in Example 4 of the present invention and the lithium-rich layered positive electrode material reported in the literature;

[0040] Figure 5 The rate performance of the button-type lithium-ion battery assembled from the high-stability lithium-rich layered positive electrode material prepared in Example 4 of the present invention and the comparative example;

[0041] Figure 6 The differential scanning calorimetry (DSC) curve of the high-stability lithium-rich layered positive electrode material prepared in Example 4 of the present invention in the delithiation state;

[0042] Figure 7 The X-ray diffraction (XRD) spectrum of the lithium-rich layered cathode material prepared in the comparative example;

[0043] Figure 8 The differential scanning calorimetry (DSC) curve of the lithium-rich layered cathode material prepared in the comparative example in the delithiation state. DETAILED DESCRIPTION

[0044] The specific implementation modes of the present invention are further described below in conjunction with examples. It should be noted that the specific implementation modes described here are only for illustrating and explaining the present invention, and are not limited to the present invention.

[0045] The present invention proposes to select different doping elements with low cost and high natural abundance to achieve synergistic doping modification at multiple sites of the lithium layer, transition metal layer and oxygen layer of the lithium-rich layered positive electrode material. The modification adopts a liquid phase chemical method, and selects a doping source with high solubility or that can be assisted by other reagents to dissolve, so as to obtain a structurally stable reinforced lithium-rich layered positive electrode material, thereby improving the electrochemical performance and thermal stability. The liquid phase synthesis method of the present invention has the advantages of simple preparation process, atomic-level dispersion of raw materials and high product purity. The main material source of the lithium-rich layered positive electrode and the anions and cations as doping sources are simultaneously put into the reaction, the main material elements and the anion doping elements are in the same phase, the doping uniformity is high, and a variety of anion and cation doping elements can be evenly distributed in the positive electrode material, and submicron single crystal positive electrode particles are obtained.

[0046] Embodiment 1:

[0047] The preparation method of high-stability lithium-rich layered positive electrode material comprises the following steps: 1.18 Na 0.01 K 0.01 Mn 0.58 Mg 0.02 Ni 0.2 O 1.98 F 0.01 Cl 0.01The stoichiometric ratio is as follows: 0.118 mol lithium hydroxide, 0.001 mol sodium acetate, 0.058 mol manganese acetate, 0.02 mol nickel nitrate, 0.001 mol potassium nitrate and 0.002 mol magnesium oxide are dispersed in 200 ml of deionized water to obtain solution A; 0.0005 mol ammonium bifluoride and 0.001 mol ammonium chloride are dispersed in 100 ml of deionized water to obtain solution B; citric acid used as a chelating agent is dispersed in 100 ml of deionized water to obtain solution C, and the total metal ions in citric acid and solution A are The molar ratio is 1:1; the prepared solution A and solution B are slowly added into solution C at the same time to obtain solution D, and the pH of solution D is adjusted to 9 with ammonia water to obtain a sol, which is heated in a water bath at 70°C for 9 hours until it is evaporated to dryness to obtain a gel, and then dried at 100°C and crushed to obtain a precursor; the obtained precursor is kept at 500°C for 4 hours in an oxygen atmosphere, and then fully ground into a uniform powder; the obtained powder is placed in an air atmosphere at 675°C for 8 hours, and then the temperature is increased to 1000°C at 5°C / min and sintered at high temperature for 15 hours to obtain a high-stability lithium-rich layered positive electrode material, such as Figure 1 Shown is the powder SEM image of the material.

[0048] Depend on Figure 1 It can be seen that, unlike the polycrystalline microsphere-type lithium-rich layered positive electrode materials disclosed in previous patents, the lithium-rich layered positive electrode material obtained in this embodiment presents single crystal particles in a polyhedral shape, which makes the material have excellent intrinsic mechanical properties and structural stability.

[0049] Embodiment 2:

[0050] The preparation of high-stability lithium-rich layered cathode material comprises the following steps: 1.18 Na 0.01 K 0.01 Mn 0.59 Zn 0.01 Ni 0.19 Mg 0.01 O 1.98 F 0.01 Cl 0.01The stoichiometric ratio is as follows: 0.118 mol lithium nitrate, 0.001 mol sodium acetate, 0.001 mol potassium hydroxide, 0.059 mol manganese acetate, 0.001 mol zinc acetate, 0.019 mol nickel acetate and 0.001 mol magnesium nitrate are dispersed in 200 ml of deionized water to obtain solution A; 0.001 mol ammonium fluoride and 0.001 mol ammonium chloride are dispersed in 20 ml of deionized water to obtain solution B; oxalic acid used as a chelating agent is dispersed in 100 ml of deionized water to obtain solution C. Oxalic acid and the total gold in the system The molar ratio of metal ions is 1:1; solution A and solution B are slowly added to solution C at the same time to obtain solution D, and ammonia water is used to adjust the pH of solution D to 7 to obtain a sol, which is heated in a water bath at 70°C for 9 hours until it is evaporated to dryness to obtain a gel, and then dried at 100°C and crushed to obtain a precursor; the precursor obtained above is maintained at 500°C for 6 hours in an air atmosphere, and then fully ground into a uniform powder; the powder obtained above is placed in an oxygen atmosphere at 750°C for 6 hours, and then the temperature is increased to 950°C at 5°C / min and sintered at high temperature for 20 hours to obtain a high-stability lithium-rich layered positive electrode material (see Figure 2 ),Depend on Figure 2 Shown is the powder XRD pattern of the material; compared with the material obtained in the comparative example, the degree of cation mixing is lower and the layered structure has better orderliness.

[0051] Embodiment 3:

[0052] The preparation method of high-stability lithium-rich layered positive electrode material comprises the following steps: 1.18 Na 0.02 Mn 0.52 Al 0.01 Ni 0.12 Cu 0.01 Co 0.13 O 1.99 Br 0.01 F 0.01The stoichiometric ratio is as follows: 0.117 mol lithium acetate, 0.002 mol sodium acetate, 0.052 mol manganese acetate, 0.001 mol aluminum nitrate, 0.012 mol nickel nitrate, 0.001 mol copper nitrate and 0.013 mol cobalt acetate are dispersed in 200 ml of deionized water to obtain solution A; 0.001 mol lithium fluoride and 0.001 mol ammonium bromide are dispersed in 20 ml of deionized water to obtain solution B; oxalic acid used as a chelating agent is dispersed in 150 ml of deionized water to obtain solution C. Oxalic acid and the total metal ions in the system are dispersed in 200 ml of deionized water to obtain solution B. The molar ratio of ions is 1.5:1; solution A and solution B are slowly added to solution C at the same time to obtain solution D, the pH of solution D is adjusted to 9 with ammonia water to obtain a sol, which is heated in a water bath at 70°C for 9 hours until evaporated to obtain a gel, which is then dried at 100°C and crushed to obtain a precursor; the precursor obtained above is maintained at 500°C for 4 hours in an oxygen atmosphere, and then fully ground into a uniform powder; the powder obtained above is placed in an oxygen atmosphere at 700°C for 10 hours, and then the temperature is increased to 975°C at 5°C / min and sintered at high temperature for 18 hours to obtain a high-stability lithium-rich layered positive electrode material.

[0053] Embodiment 4:

[0054] The preparation method of high-stability lithium-rich layered positive electrode material comprises the following steps: 1.18 K 0.02 Mn 0.53 Zr 0.01 Ni 0.13 Co 0.12 Cu 0.01 O 1.98 S 0.01 Br 0.01The stoichiometric ratio is as follows: 0.118 mol lithium acetate, 0.002 mol potassium nitrate, 0.053 mol manganese acetate, 0.001 mol zirconium nitrate, 0.013 mol nickel nitrate, 0.001 mol copper nitrate and 0.012 mol cobalt nitrate are dispersed in 200 ml of deionized water to obtain solution A; 0.001 mol 2-Mercaptopropionic acid and 0.001 mol of ammonium bromide are dispersed in 20 ml of deionized water to obtain solution B; citric acid used as a chelating agent is dispersed in 150 ml of deionized water to obtain solution C, and the molar ratio of citric acid to the total metal ions in the system is 1.5:1; solution A and solution B are slowly added to solution C at the same time to obtain solution D, and ammonia water is used to adjust the pH of solution D to 9 to obtain a sol, which is heated in a 70°C water bath for 9 hours until evaporated to dryness to obtain a gel, and then dried at 100°C and crushed to obtain a precursor; the precursor obtained above is maintained at 450°C for 4 hours in an oxygen atmosphere, and then fully ground into a uniform powder; the powder obtained above is placed in an oxygen atmosphere at 650°C for 8 hours, and then the temperature is increased to 950°C at 5°C / min and high-temperature sintered for 12 hours to obtain a high-stability lithium-rich layered positive electrode material.

[0055] Comparative Example 1:

[0056] The lithium-rich layered cathode material is obtained by a sol-gel method and subsequent high-temperature sintering, comprising the following steps: 1.2 Mn 0.54 Ni 0.13 Co 0.13 O2 represents the stoichiometric ratio, 0.12 mol lithium acetate, 0.054 mol manganese acetate, 0.013 mol nickel nitrate and 0.013 mol cobalt nitrate are dispersed in 200 ml deionized water to obtain solution A; citric acid used as a chelating agent is dispersed in 150 ml deionized water to obtain solution B, and the molar ratio of citric acid to the total metal ions in the system is 1.5:1; solution A is slowly added to solution B to obtain solution C, and ammonia water is used to adjust the pH of solution C to 9 and obtain a sol, which is heated in a water bath at 70°C for 9 hours until it is evaporated to dryness to obtain a gel, and then dried at 100°C and crushed to obtain a precursor; the precursor obtained in the previous step is maintained at 450°C for 4 hours in an oxygen atmosphere, and then fully ground into a uniform powder; the powder obtained in the previous step is placed in an air atmosphere at 650°C for 8 hours, and then the temperature is increased to 950°C at 5°C / min and sintered at high temperature for 15 hours to obtain a lithium-rich layered positive electrode material (see Figure 7 ),like Figure 7 The powder XRD pattern of the material shown above shows that the degree of cation mixing in the material is high and the layered structure is poorly ordered.

[0057] Comparative Example 2:

[0058] The preparation method of high-stability lithium-rich layered positive electrode material comprises the following steps:1.18 K 0.02 Mn 0.54 Ni 0.13 Co 0.13 According to the stoichiometric ratio represented by O2, 0.118 mol of lithium acetate, 0.002 mol of potassium nitrate, 0.054 mol of manganese acetate, 0.013 mol of nickel nitrate and 0.013 mol of cobalt nitrate are dispersed in 200 ml of deionized water to obtain solution A; citric acid used as a chelating agent is dispersed in 150 ml of deionized water to obtain solution B, and the molar ratio of citric acid to the total metal ions in the system is 1.5:1; solution A is slowly added to solution B to obtain solution C, and the pH of solution C is adjusted to 9 with ammonia water to obtain a sol, which is heated in a water bath at 70°C for 9 hours until evaporated to obtain a gel, and then dried at 100°C and crushed to obtain a precursor; the precursor obtained above is maintained at 450°C for 4 hours in an oxygen atmosphere, and then fully ground into a uniform powder; the powder obtained above is placed in an oxygen atmosphere at 650°C for 8 hours, and then the temperature is increased to 950°C at 5°C / min and sintered at high temperature for 12 hours to obtain a high-stability lithium-rich layered positive electrode material.

[0059] Comparative Example 3:

[0060] The preparation method of high-stability lithium-rich layered positive electrode material comprises the following steps: 1.2 Mn 0.53 Zr 0.01 Ni 0.13 Co 0.12 Cu 0.01 The stoichiometric ratio represented by O2 is as follows: 0.12 mol lithium acetate, 0.053 mol manganese acetate, 0.001 mol zirconium nitrate, 0.013 mol nickel nitrate, 0.001 mol copper nitrate and 0.012 mol cobalt nitrate are dispersed in 200 ml of deionized water to obtain solution A; citric acid used as a chelating agent is dispersed in 150 ml of deionized water to obtain solution B, and the molar ratio of citric acid to the total metal ions in the system is 1.5:1; solution A is slowly added Solution C is obtained from solution B, and the pH value of solution C is adjusted to 9 with ammonia water to obtain a sol, which is heated in a water bath at 70°C for 9 hours until evaporated to dryness to obtain a gel, which is then dried at 100°C and crushed to obtain a precursor; the precursor obtained above is maintained at 450°C for 4 hours in an oxygen atmosphere, and then fully ground into a uniform powder; the powder obtained above is placed in an oxygen atmosphere at 650°C for 8 hours, and then the temperature is increased to 950°C at 5°C / min and high-temperature sintered for 12 hours to obtain a high-stability lithium-rich layered positive electrode material.

[0061] Comparative Example 4:

[0062] The preparation method of high-stability lithium-rich layered positive electrode material comprises the following steps: 1. Mn 0.54Ni 0.13 Co 0.1 3O 1.98 S 0.01 Br 0.01 The stoichiometric ratio is as follows: 0.12 mol lithium acetate, 0.054 mol manganese acetate, 0.013 mol nickel nitrate and 0.013 mol cobalt nitrate are dispersed in 200 ml of deionized water to obtain solution A; 0.001 mol 2-Mercaptopropionic acid and 0.001 mol of ammonium bromide are dispersed in 20 ml of deionized water to obtain solution B; citric acid used as a chelating agent is dispersed in 150 ml of deionized water to obtain solution C, and the molar ratio of citric acid to the total metal ions in the system is 1.5:1; solution A and solution B are slowly added to solution C at the same time to obtain solution D, and ammonia water is used to adjust the pH of solution D to 9 to obtain a sol, which is heated in a 70°C water bath for 9 hours until evaporated to dryness to obtain a gel, and then dried at 100°C and crushed to obtain a precursor; the precursor obtained above is maintained at 450°C for 4 hours in an oxygen atmosphere, and then fully ground into a uniform powder; the powder obtained above is placed in an oxygen atmosphere at 650°C for 8 hours, and then the temperature is increased to 950°C at 5°C / min and high-temperature sintered for 12 hours to obtain a high-stability lithium-rich layered positive electrode material. Test example: Take the samples obtained in Example 4, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4, respectively, mix with binder PVDF and conductive agent Super P in a mass ratio of 8:1:1, add a certain amount of 1-methyl-2-pyrrolidone (NMP) and stir on a magnetic stirrer for 4 hours to make a paste, then apply it to aluminum foil, place it in a vacuum drying oven at 110°C and dry it for 12 hours, cut the evenly coated part on the aluminum foil into a disc with a diameter of 12 mm as a working electrode, and then place it in a vacuum drying oven at 110°C and dry it for 6 hours. The above operations are all completed in a drying room with a dew point higher than 50°C, and finally transfer the dried working electrode to an argon glove box for assembly. The pp three-layer microporous membrane is used as the diaphragm, the metal lithium sheet is used as the negative electrode, and the electrolyte is a 1mol / L LiPF6 / EC:DEC=1:1 (volume ratio) solution. The assembled battery is left to stand for 12 hours before testing. In a thermostat at 30°C, the battery was subjected to rate charge and discharge tests using a Land test system, with a voltage range of 2.0-4.7V, and pre-cycled 4 times at a rate of 0.1C (1C = 200mA / g), followed by a long cycle at a rate of 1C. Figure 3 As shown, the prepared Li 1.18 K 0.02 Mn 0.53 Zr 0.01 Ni 0.13 Co 0.12 Cu 0.01 O 1.98 S 0.01 Br 0.01After the material is cycled 100 times under the above test conditions, the capacity retention rate is as high as 93%, and the residual discharge capacity is as high as 208mAh / g, showing excellent cycle performance. In comparison, the capacity retention rates of the materials obtained in Comparative Examples 1, 2, 3 and 4 after 100 cycles are 81%, 89%, 87% and 90%, respectively, and the residual discharge capacities are only 162mAh / g, 193mAh / g, 185mAh / g and 178mAh / g, respectively. It can be seen that the lithium-rich layered positive electrode material of the present invention adopts different low-cost, high-natural abundance anions and cations to dope the lithium layer, transition metal layer and oxygen layer respectively, and the elements are added at the same time to synergistically modify and enhance the electrochemical redox reversibility of the lithium-rich layered positive electrode material, inhibit the transformation of the layered structure to the spinel structure during the cycle, and improve the structural stability of the material. It has high initial charge and discharge efficiency, high reversible specific capacity, long cycle life, outstanding rate performance and high thermal stability; at the same time, it is comparable to the performance of lithium-rich layered positive electrode materials reported at home and abroad (see Figure 4 ) compared with the above materials, the material performance of the present invention is at the leading level.

[0063] like Figure 5 , 6 and Figure 8 The material's rate performance diagram and the material's delithiation state DSC diagram. Figure 6 and Figure 8 The lithium-rich layered positive electrode material obtained in this embodiment exhibits higher thermal stability.

[0064] Above Figure 4 The lithium-rich layered cathode materials reported at home and abroad are respectively in the literature 1 Adv. Mater. 2023, 35, e2208726; literature 2 Nat. Energy 2019, 4, 1049-1058; literature 3 Adv. Mater. 2023, 2307138; literature 4 Adv. Mater. 2022, 34, e2109564; literature 5 Angew. Chem. Int. Ed. 2021, 60, 23248-23255; literature 6 Angew. Chem. Int. Ed. 2020, 59, 7778-7782; literature 7 Adv. Energy Mater. 2022, 12, 2202341; literature 8 Nano Energy 2022, 98, 107169.

Claims

1. A highly stable lithium-rich layered cathode material, characterized in that: The lithium-rich layered cathode material is Li 1+x-a A a TM 1-x- b B b O 2-c C c , where 0 < x < 1, 0 < a ≤ 0.1, 0 < b ≤ 0.1, 0 < c ≤ 0.1; wherein, A is a doping element in the lithium layer, B is a doping element in the transition metal (TM) layer, and C is a doping element in the oxygen layer.

2. The high-stability lithium-rich layered positive electrode material according to claim 1, characterized in that: The A is selected from one or more monovalent metal ions, TM is selected from one or more of Mn, Ti, Fe, Co, and Ni, B is selected from one or more of B, Mg, Al, Si, P, Ca, Cu, Zn, Zr, and Se, and C is selected from one or more of S, F, Cl, Br, and I.

3. The high-stability lithium-rich layered positive electrode material according to claim 2, characterized in that: The A is selected from one or more of Na, K, Rb, and Cs.

4. A method for preparing a high-stability lithium-rich layered positive electrode material according to claim 1, characterized in that: According to the stoichiometric ratio of the materials, the main source in the positive electrode material and the doping elements in each main source are added simultaneously, and a high-stability lithium-rich layered positive electrode material is prepared by a sol-gel method; wherein the main source is a lithium source and a transition metal source.

5. The method for preparing a high-stability lithium-rich layered positive electrode material according to claim 4, characterized in that: 1) Precursor synthesis: The lithium source in the lithium layer, the transition metal source in the transition layer and the doping elements of the above two metal layers are prepared according to Li 1+x-a A a TM 1-x-b B b O 2-c C c The stoichiometric ratio in the chemical formula is uniformly dispersed in deionized water to obtain solution A; the element source used for oxygen layer doping is Li 1+x-a A a TM 1-x-b B b O 2-c C c The stoichiometric ratio is uniformly dispersed in deionized water to obtain solution B; a soluble organic acid source used as a chelating agent is uniformly dispersed in deionized water to obtain solution C; Slowly adding solution A and solution B into solution C at the same time to obtain solution D, adjusting the pH of solution D to 6-10, drying and crushing to obtain a precursor; 2) Precursor sintering: The precursor is placed in a specific atmosphere at 400-600°C for 3-8 hours, and then fully ground into a uniform powder; the resulting powder is placed in a specific atmosphere at 600-800°C for 3-12 hours, and then heated to 800-1000°C for high-temperature sintering for 8-20 hours to obtain a highly stable lithium-rich layered cathode material (Li 1+x-a A a TM 1-x-b B b O 2-c C c ).

6. The method for preparing a high-stability lithium-rich layered positive electrode material according to claim 4 or 5, characterized in that: The lithium source is one or more of lithium hydroxide, lithium citrate, lithium nitrate, lithium acetate, lithium sulfate, lithium fluoride, and lithium carbonate; The transition metal source is one or more of acetates, nitrates or hydroxides containing Mn, Fe, Co and Ni elements; The transition metal source containing the Ti element is one or more of tetrabutyl titanate, titanium hydroxide, ammonium titanyl oxalate and titanium dioxide.

7. The method for preparing a high-stability lithium-rich layered positive electrode material according to claim 4 or 5, characterized in that: The doping element of the lithium layer can be selected from one or more of acetates, nitrates, carbonates or hydroxides containing Na, K, Rb or Cs elements; The doping element of the transition metal layer can be selected from one or more of acetates, nitrates, oxides or hydroxides containing Mg, Al, Ca, Cu, Zn and Zr. The doping element B of the transition metal layer may be one or more of boric acid, boron oxide and ammonium pentaborate; The doping element Si of the transition metal layer can be selected from one or more of lithium metasilicate and quaternary ammonium silicate. The doping element P of the transition metal layer can be selected from one or more of phosphoric acid, pyrophosphoric acid, diammonium hydrogen phosphate, ammonium phosphate and phosphorus pentoxide. The doping element Se of the transition metal layer may be selected from one or more of selenium dioxide, selenium trioxide, selenic acid and ammonium selenate; The doping element of the oxygen layer may be a soluble ammonium salt or lithium salt containing F, Cl, Br, or I; The doping element S of the oxygen layer may be selected from one or more of 2-mercaptopropionic acid, lithium sulfide, ammonium sulfide, and thiourea.

8. The method for preparing a high-stability lithium-rich layered positive electrode material according to claim 5, characterized in that: The soluble organic acid source is one or a mixture of tartaric acid, oxalic acid, citric acid, and maleic acid, and the molar ratio of the carboxyl group in the organic acid to the total metal ions in the precursor is (1-10):

1.

9. The method for preparing a high-stability lithium-rich layered positive electrode material according to claim 5, characterized in that: The solution D is adjusted to a pH value and then heated in a water bath at 60-100° C. for 6-20 h, evaporated to dryness, dried at 80-140° C., and crushed to obtain a precursor.

10. The method for preparing a high-stability lithium-rich layered positive electrode material according to claim 5, characterized in that: In the step 2), the specific atmosphere is oxygen or air, and the heating rate is 0.5-5°C / min.

Citation Information

Patent Citations

  • Doped modified metal pyrophosphate positive electrode material

    CN109980186A

  • Anion-cation co-doped modified lithium-rich manganese composite positive electrode material and preparation method thereof

    CN111370686A

  • Lithium-rich layered positive electrode material, preparation method thereof, battery positive electrode formed by lithium-rich layered positive electrode material and battery

    CN113097475A

  • Alkaline earth / rare earth metal-containing high-voltage layered structure positive electrode material and preparation method thereof

    CN114122346A

  • Positive electrode active material for lithium secondary battery, method for preparing same, and lithium secondary battery including same

    CN115461895A

Cited By

  • Positive electrode material and preparation method and application thereof

    CN120432512A

  • A positive electrode material, a preparation method and application thereof

    CN120432512B